Multicomponent reaction for the synthesis of novel fluorinated 2-amino-4H-benzo[g]chromene-5,10-dione-3-carbonitriles - Ha Thanh, Nguyen; Phuong, Hoang Thi; Giang, Le Nhat Thuy; Quynh Giang, Nguyen Thi; Tuan Anh, Nguyen; Tuyet Anh, Dang Thi; Tuyen, Nguyen Van (Vietnam Journal of Science and Technology, 2023)
Chromene is a significant class of heterocyclic compounds prossessing a simple structure as well as important biological activities. Many studies have been done to find new approaches for the preparation of chromene derivatives. Notably, the introduction of fluorine into heterocyclic molecules resulted in a significant improvement of their biological activities. In this study, a simple, straightforward, and highly efficient microwave-assisted three-component synthesis of novel 2-amino-4H-benzo[g]chromene-5,10-dione-3-carbonitrile derivatives bearing fluorine atoms has been developed using 1,4-diazabicyclo[2.2.2]octane (DABCO) as an eco-friendly catalyst, and acetonitrile as a solvent. Starting from 2-hydroxy-1,4-dihydronaphthalene-1,4-dione, malononitrile, and fluorinated aromatic aldehyde, 2-amino-4H-benzo[g]chromene-5,10-dione-3-carbonitrile derivatives have been afforded in good yields (71 – 76 %). The plausible reaction mechanism was described. Products were synthesized through a sequential Knoevenagel condensation, Michael addition, intramolecular cyclization, and [1,3]-hydrogen shift step. The structure of products was completely elucidated  by 1H NMR, 13C NMR, and mass spectra. The particularly valuable feature of this process is mild reaction conditions, short reaction times, and good yields.